EMBEDDING ISLAMIC SPIRITUAL VALUES IN THEMATIC TEACHING FOR PRIMARY ISLAMIC SCHOOLS - Basit, Abdul; Remiswal, Remiswal; Nelwati, Sasmi; Zalnur, Muhammad; Ahmad, Aprizal (TA`DIBUNA, 2025)
This study explores the integration of Islamic spiritual values within thematic instruction in Madrasah Ibtidaiyah Negeri (MIN) across Padang City, Indonesia. As expectations grow for Islamic primary schools to balance academic achievement with the cultivation of religious character, understanding how to embed spiritual values into general subjects becomes increasingly vital. The research aims to identify the spiritual values adopted, examine their implementation in classroom practices, and assess their impact on students’ holistic development. Employing a qualitative–descriptive approach, data were collected from six MIN through classroom observations, teacher interviews, lesson plan analysis, and surveys of teachers and parents (n = 50). The findings reveal eight core values—tawakkul (trust in God), ikhlas (sincerity), amanah (responsibility), rahmah (compassion), syukur (gratitude), tauhid (oneness of God), istiqamah (steadfastness), and adab (ethical conduct)—integrated across multiple subjects. Strategies include spiritual reflection, contextual prayers, Islamic storytelling, and social service activities. The results indicate improvements in students’ moral behavior and sense of responsibility, demonstrating that spiritually based thematic learning effectively fosters both academic competence and spiritual maturity.